Sifat Balok Glulam Kayu Terentang (Campnosperma auriculatum (Blume) Hook.F.) Berdasarkan Jumlah Lamina: Properties of Glue laminated Timber Beams from Terentang Wood (Campnosperma auriculatum (Blume) Hook.F.) Based on the Number of Laminae - Sirait, Hizkia Ireni; oktoberyani christy, Eva; Indrayanti, Lies; Pidjath, Chartina; Penyang, Penyang; Koroh, Desy Natalia (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
The purpose of this study was to determine the effect of the number of laminae on the physical and mechanical properties of terentang wood glulam beams. Three types of glulam beams were manufactured with 3, 4, and 5 laminae, then glued using PVAc (polyvinyl acetate) adhesive with a glue spread of 200 g/m², vacuumed using the vacuum bagging method, and left in the vacuum bag for 24 hours. As a comparator, solid beams with the same cross-section (50 mm × 50 mm) were also prepared. The results indicated that the number of laminae had a very significant effect on water content and specific gravity, as well as a significant effect on the Modulus of Elasticity (MoE) and Modulus of Rupture (MoR). Tukey's test confirmed that the MoE and MoR of 3-layer glulam beams were not significantly different from those of the solid beam. This suggests that 3-layer glulam beams had mechanical performance equal to the solid beam and relatively better than 4- and 5-layer glulam beams. Increasing the number of laminae tended to decrease the MoE and MoR values of glulam beams. Based on the Indonesian wood strength classification, solid beams fall into strength class III, as do 3-layer and 5-layer glulam beams. The 4-layer glulam beam was classified as strength class IV. All glulam beams indicate no improvement in class compared to the solid beam.